Oxidative Imbalance and Kidney Damage in Cafeteria Diet-Induced Rat Model of Metabolic Syndrome: Effect of Bergamot Polyphenolic Fraction - Daniele La Russa; Francesca Giordano; Alessandro Marrone; Maddalena Parafati; Elzbieta Janda; Daniela Pellegrino (MDPI AG, 2019)
Obesity is a potent risk factor for kidney disease as it increases the possibility of developing diabetes and hypertension, and it has a direct impact on the development of chronic kidney disease and end-stage renal disease. In this study, we tested the effect of bergamot polyphenolic fraction in a cafeteria with diet-fed rats, an excellent experimental model for studying human metabolic syndrome, as it is able to induce severe obesity with insulin resistance and high plasma triglyceride levels more efficiently than a traditional lard-based high-fat diet used in rodent models. We analyzed the plasmatic oxidative balance by photometric tests, and the expression of cytoplasmic antioxidant enzymes (superoxide dismutase 1 and glutatione S-tranferasi P1) and apoptotic markers (Caspase 8 and 9) in kidney tissues by Western blot analysis. Our results clearly showed that the cafeteria diet induces a marked pro-oxidant effect: significant reduction of plasmatic antioxidant capacity; downregulation of cytoplasmic antioxidant enzymes expression; and activation of apoptotic pathways. All these hallmarks of redox disequilibrium were mitigated by treatment with polyphenolic fraction of bergamot, highlighting its antioxidant effect in the metabolic syndrome. Our data show that the link between obesity and renal damage could be represented by oxidative stress.